Memperkuat Daya Tarik Setu Babakan: Integrasi Strategi Pemasaran Untuk Meningkatkan Kunjungan Wisatawan - Anisatul Auliya; Uggasena Ariya Saputra; Muhammad Rifky; Muhammad Faza Alghifari; Muhammad Iqbal Wily Mahmud; Fredy Yohannes Noriaga; Laura Aurelia Tedjasukmana (STIE Pariwisata API Yogyakarta, 2024)
This research aims to conduct a SWOT analysis and develop an integrated marketing strategy to enhance Setu Babakan's appeal as a Betawi cultural destination. The study uses a descriptive qualitative method with primary data from official Indonesian government releases and secondary data from various publications and the internet. The SWOT analysis reveals strengths in natural, educational, and cultural tourism, weaknesses in public understanding and supervision, opportunities to increase community income and attract tourists, and threats from competition with other destinations. Based on this analysis, an integrated marketing strategy is formulated, focusing on target audiences like families, culture enthusiasts, nature tourists, and educational visitors. This strategy involves developing attractive tourism products, setting affordable prices, improving accessibility, utilizing digital marketing through websites and social media platforms, fostering partnerships with local governments, private sectors, and communities, and enhancing service quality and infrastructure. The recommended marketing integration aims to boost Setu Babakan's appeal as a Betawi cultural destination and attract more tourists.